Nuclear pre-mRNA Processing in Plants - Reddy, A. S. N.; Golovkin, Maxim V.; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2008)
In recent years nuclear pre-mRNA processing has taken center stage as an important regulator of gene expression and ultimately growth and development. Large-scale genome and cDNA sequencing projects together with bioinformatic analyses of these sequences have revealed that alternative splicing of pre-mRNAs contributes greatly to transcriptome and proteome complexity in eukaryotes. During the last few years, tremendous progress has been made in understanding various aspects of pre-mRNA processing including alternative splicing and its importance in plant growth and development as well as in plant responses to hormones and stresses. This book, with contributions from leading scientists in this area, summarizes recent advances in nuclear pre-mRNA processing in plants. It provides researchers in the field, as well as those in related areas, with an up-to-date and comprehensive, yet concise, overview of the current status and future potential of this research in understanding plant biology.
Spliceosomal Proteins in Plants -- Analysis of Alternative Splicing in Plants with Bioinformatics Tools -- Splice Site Requirements and Switches in Plants -- U12-Dependent Intron Splicing in Plants -- Plant SR Proteins and Their Functions -- Spatiotemporal Organization of Pre-mRNA Splicing Proteins in Plants -- Regulation of Splicing by Protein Phosphorylation -- mRNA Cap Binding Proteins: Effects on Abscisic Acid Signal Transduction, mRNA Processing, and Microarray Analyses -- Messenger RNA 3? End Formation in Plants -- State of Decay: An Update on Plant mRNA Turnover -- Regulation of Flowering Time by RNA Processing -- Alternative Splicing in Plant Defense -- Nuclear RNA Export and Its Importance in Abiotic Stress Responses of Plants -- Regulation of Alternative Splicing of Pre-mRNAs by Stresses -- Intron-Mediated Regulation of Gene Expression -- The Role of the Plant Nucleolus in Pre-mRNA Processing.
Keywords: Plant science; Botany; Plant Sciences